Differences in Nutrition Knowledge Between Junior High School Students who Receive Nutrition Education Using Offline and Online Booklet Media - Hastuti, Anindra Retno; Rakhma, Luluk Ria (Jurnal Indonesia Sosial Sains, 2025)
The increasing prevalence of adolescent nutritional problems, particularly those related to breakfast habits and obesity, necessitates effective nutrition education strategies that can be implemented both in traditional face-to-face settings and through digital platforms. Contemporary educational approaches must adapt to technological advances while maintaining pedagogical effectiveness, making it crucial to evaluate the comparative efficacy of different delivery methods for nutrition education among adolescents. This study aims to determine the difference in nutrition knowledge levels among junior high school students who received nutrition education using booklet media through offline (luring) and online (daring) methods. The research design employed was a quasi-experimental approach with a nonequivalent control group design, involving 60 eighth-grade students from SMP Al-Islam 1 Surakarta and SMP Muhammadiyah 5 Surakarta. Participants were divided into a control group (offline) and an experimental group (online). Data were collected using a questionnaire consisting of 20 validated questions regarding the importance of breakfast, administered before (pretest) and after (posttest) the intervention. Data analysis was conducted using the Wilcoxon test for within-group comparisons and the independent sample t-test for between-group comparisons. The results showed an average difference in students' knowledge scores of 19.67 for the offline method and 19.83 for the online method, with a p-value of 0.904, indicating no significant difference between the two methods. These findings suggest that both methods are equally effective in improving students' nutrition knowledge, making them viable alternatives for nutrition education in schools.